Do older patients with acute or subacute subdural hematoma benefit from surgery?. (2nd January 2019) - Bus, Sander; Verbaan, Dagmar; Kerklaan, Bertjan J.; Sprengers, Marieke E.S.; Vandertop, William P.; Stam, Jan; Bouma, Gerrit J.; van den Munckhof, Pepijn
Abstract: Purpose: According to the international guidelines, acute subdural hematomas (aSDH) with a thickness of >10 mm, or causing a midline shift of >5 mm, should be surgically evacuated. However, high mortality rates in older patients resulted in ongoing controversy whether elderly patients benefit from surgery. We identified predictors of outcome in a single-centre cohort of elderly patients undergoing surgical evacuation of aSDH or subacute subdural hematoma (saSDH). Materials and methods: This retrospective study included all patients aged ≥65 years undergoing surgical evacuation of aSDH/saSDH from 2000 to 2015. One-year outcome was dichotomized into favourable (Glasgow Outcome Scale (GOS) 4–5) and unfavourable (GOS 1–3). Predictors of outcome were identified by analysing patient characteristics. Results: Eighty-four patients aged ≥65 years underwent craniotomy for aSDH/saSDH during the 16 year time period. Twenty-five percent regained functional independence, 11% survived severely disabled, and 64% died. Most patients died of respiratory failure following withdrawal of artificial respiration or following restriction of treatment. Age of the SDH or Glasgow Coma Scores ≤8/intubation did not predict unfavourable outcome. All patients with bilaterally absent pupillary light reflexes died, also those who still exhibited one normal-sized pupil. Conclusion: The low number of operated patients per year probably suggests that this cohort represents a selection of patients who were judged to have good chances of favouring from surgery. Functional independence at one-year follow-up was reached in 25% of patients, 64% died. Patients with bilaterally absent pupillary light reflexes did not benefit from surgery. The tendency to restrict treatment because of presumed poor prognosis may have acted as a self-fulfilling prophecy.